2023
DOI: 10.4028/p-nlb9zf
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Effects of Electroplating Conditions on TEMPO-Oxidized Cellulose Nanofiber Composited Nickel Electroplated Films

Makoto Iioka,
Wataru Kawanabe,
Tatsuya Kobayashi
et al.

Abstract: The effects of plating conditions on nickel (Ni) electroplated films composited with 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO)-oxidized CNFs (CNFs) were investigated. Plating experiments were performed by varying the amount of CNFs added to the Watt's bath, the current density, and the stirring speed. The plated film obtained at 3 g/L, 2.5 A/cm2, and 300 rpm of them respectively, reached an average 483 HV of the surface hardness, which was the highest in this study. The surface hardness of the conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 8 publications
3
7
4
Order By: Relevance
“…The detection of several mass% values on the plated film without CNF was considered to be background noise [ 2 ]. In our previous study [ 4 ], the content of cellulose showed an increasing trend with the increase in CNF in the range of 1–3 g/L; thus, the trend in this study is different from that.…”
Section: Resultscontrasting
confidence: 80%
See 4 more Smart Citations
“…The detection of several mass% values on the plated film without CNF was considered to be background noise [ 2 ]. In our previous study [ 4 ], the content of cellulose showed an increasing trend with the increase in CNF in the range of 1–3 g/L; thus, the trend in this study is different from that.…”
Section: Resultscontrasting
confidence: 80%
“…Figure 6 shows the appearance of the plated films. As in previous studies [ 2 , 3 , 4 ], the plated film without CNF was matte, and the plated film with CNF was bright, while the plated film with CNF showed uneven brightness under the conditions where 2 and 3 g/L of CNF were added.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations